Apakah Eko-Feminisme Mempengaruhi Kualitas Pengungkapan ESG dan Kinerja Perbankan - Gumilar sukmawan; Khomsiyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the relationship between the nature of ecofeminism of female directors and ESG disclosure and the nature of ecofeminism on banking performance. This research uses how many female directors there are in a bank as an independent variable, while the dependent variables are ESG disclosure and banking performance as measured by ROA.This research uses a sample of conventional banks listed on the Indonesia Stock Exchange from 2021 to 2023. A total of 43 conventional banks were taken as samples, and a purposive sampling method was used. This research uses linear regression analysis using IBM SPSS 27.The results of this research found that female directors have no effect on ESG disclosures, while female directors have an effect on banking performance.